On Vehicle Stabilization Under Saturation Constraints by Linear Quadratic Regulator - Mulia Vania Katherine; Djamari Djati Wibowo; Veza Ibham; Ignatius Pulung Nurprasetio (University of Muhammadiyah Malang, 2022)
The stability of a four-wheel vehicle is an issue widely discussed. As an effort to reduce accidents involving four-wheel vehicles, many studies have been conducted to develop a vehicle stability control system. So far, all studies utilize vehicle lateral dynamics model as the reference to derive the desired states. However, defining the desired states using steady-state cornering values may yield instability due to changes in tire cornering stiffness. This paper proposes a simple vehicle stability control system that could stabilize the vehicle and allow tracking of a desired state under the case of vehicle instability due to reduced rear tire cornering stiffness. The controllers are designed using Linear Quadratic Regulator (LQR) technique and combined with the servo control system to track a reference state. Simulations are performed in MATLAB to validate the controller’s performance with and without controller constraint. Results show that the controller successfully stabilizes the vehicle and tracks the desired state.